Archaeobotany in Greece - Livarda, Alexandra (Cambridge University Press, 2014)
This paper provides a brief overview of the history and main achievements of archaeobotanical work in Greece to date, with the aim of highlighting its potential and creating a framework in which future work can be contextualized. The term “archaeobotany” is used here in its narrow sense, referring to the study of plant macroremains, such as seeds, fruits and other plant parts, and excluding charcoal studies or “anthracology” and analyses of microremains (for example pollen, phytoliths), which have developed to become separate subdisciplines.